Sistem Informasi Surat Masuk dan Surat Keluar Menggunakan Metode Agile pada DPRD Provinsi Kalimantan Barat - Trisna Yuniarsih; Istikoma, Istikoma; Huyearka Usady (Lembaga Pengembangan Kinerja Dosen, 2025)
Information systems are an important component in supporting the efficiency of a government agency. Previously, the West Kalimantan Provincial DPRD still managed incoming and outgoing mail manually, such as delivering letters, creating letter agendas using Microsoft Word documents, which made the archiving process, data search, and letter tracking less effective. This study aims to Design and build a website-based incoming and outgoing mail information system to facilitate digital letter administration management. The system development method used is the Agile method, which emphasizes iterative and collaborative processes between developers and Users. System testing was carried out using the black box testing method to ensure that all features function according to User needs. The results of the User Acceptance Test (UAT) showed that the system obtained a satisfaction level of 88%, which is included in the